Product variety and the gains from international trade - Feenstra, Robert C. (MIT Press, 2010)
Feenstra considers the consumer benefits from having access to new import varieties of differentiated products, and examines a recent method to estimate the elasticity of substitution (the extent of differentiation across products) and to use that information to construct the gains from import variety.